2016
DOI: 10.1002/cssc.201600649
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration of Glucose to 5‐Hydroxymethylfurfural Using Nb‐doped Tungstite

Abstract: Dehydration of glucose to 5‐hydroxymethylfurfural (HMF) remains a significant problem in the context of the valorization of lignocellulosic biomass. Hydrolysis of WCl6 and NbCl5 leads to precipitation of Nb‐containing tungstite (WO3⋅H2O) at low Nb content and mixtures of tungstite and niobic acid at higher Nb content. Tungstite is a promising catalyst for the dehydration of glucose to HMF. Compared with Nb2O5, fewer by‐products are formed because of the low Brønsted acidity of the (mixed) oxides. In water, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…[32] For instance, W-Zr mixed oxidesc an efficiently convert cellulose to lactic acid, [33] ethyl lactate can efficiently be obtained from triose sugars over Sn/Al oxide, [34] and glucose can (through fructose) be dehydrated into 5-hydroxymethylfurfural with Nbdoped WO 3 . [35] In our previous work, Al-Zr mixed oxide was confirmed to be an efficient catalystf or the production of GVL from ethyl levulinate, [23] and in continuationo fo ur research on CTH of biomass-derived chemicals, we expecteda lso such catalysts to be active in CTH of FF to FAOL. Solid materials with magnetic properties are highly interesting catalyst supports because they allow easy catalyst separation and recycling from liquid reactionm ixturesb ya pplying an external magnetic field.…”
Section: Introductionmentioning
confidence: 72%
“…[32] For instance, W-Zr mixed oxidesc an efficiently convert cellulose to lactic acid, [33] ethyl lactate can efficiently be obtained from triose sugars over Sn/Al oxide, [34] and glucose can (through fructose) be dehydrated into 5-hydroxymethylfurfural with Nbdoped WO 3 . [35] In our previous work, Al-Zr mixed oxide was confirmed to be an efficient catalystf or the production of GVL from ethyl levulinate, [23] and in continuationo fo ur research on CTH of biomass-derived chemicals, we expecteda lso such catalysts to be active in CTH of FF to FAOL. Solid materials with magnetic properties are highly interesting catalyst supports because they allow easy catalyst separation and recycling from liquid reactionm ixturesb ya pplying an external magnetic field.…”
Section: Introductionmentioning
confidence: 72%
“…5). Previous work shows that doping WO 3 with niobium increased the Brønsted acidity of the material [33]. The exchange of Lewis acidic W VI cations by Nb V species induces a charge defect which is compensated by acidic protons, thus increasing the amount of Brønsted acid sites (BAS).…”
Section: Resultsmentioning
confidence: 99%
“…These materials are abundant and cheap, and express water-tolerant Lewis acid sites and tunable acid-base properties with promising glucose-upgrading abilities [31,32]. Recently, we have shown that tungstite (WO 3 ·H 2 O) is also a viable contender [33]. The material comprises distorted WO 5 ·H 2 O octahedra, which share 4 equatorial corner oxygens to form a stacked sheet-like material with a low surface area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dehydration reaction is an important and also challenging reaction for the synthesis of fine chemicals from biomass ,. Dehydration of cyclohexanol retards the rate of hydroalkylation of phenol .…”
Section: Catalytic Activity Of Each Catalysts and Regeneration Of Nb1p3mentioning
confidence: 94%